CFD investigation of the statistical characteristics of NOx photo-catalytic degradation in a glass curtain wall in hazy winter weather. (October 2019) - Shen, Huiyuan; Du, Fangli; Liu, Yanhua; Huang, Yu; Zhang, Yufei; Wang, Zhenyu; Wu, Qi; He, Wenbo
Highlights: The glass curtain wall was combined with the photo-catalytic technology to reduce the NOx concentration and prevent NOx from entering the residential rooms. In the photo-catalytic glass curtain wall, the statistical distribution of NOx concentration was simulated by the CFD simulation technology. Between the NOx statistical concentration and the turbulence intensity generated by the swirling flow, relationships were obtained in the curtain wall. Close to the swirling flow region, the optimal functional relationship was presented as CR = 0.85 + 0.1e−I, where CR was the NOx relative concentration and I was the turbulence intensity Abstract: In the hazy winter weather, in order to know the main factors impacting the statistical characteristics of NOx degradation in a photo-catalytic breathable glass curtain wall, CFD simulation technology was used to research the statistical characteristics of NOx migration from the outdoor environment to the indoor environment. In this paper, the relationship between swirling flow, temperature and NOx concentration distribution was emphatically investigated. The simulation results showed that the temperature distribution had no direct relationship with the statistical distribution of NOx concentration, while the statistical distribution of NOx concentration had a direct correlation with the swirling flow. The existence of the complex statistical characteristics for swirling flow and NOx concentration had been identified inside the photo-catalytic breathable glass curtain wall. Furthermore, a relationship was observed between the swirling flow, turbulence and NOx concentration in the glass curtain wall. The results showed that one simple functional relationship existed between the NOx statistical concentration and the turbulence intensity generated by the swirling flow in the curtain wall. Moreover, close to the swirling flow region, the optimal functional relationship was presented as CR  = 0.85 + 0.1e − I, where CR was the NOx relative concentration and I was the turbulence intensity.